Method and equipment for testing fibrillation performance of real silk or tencel fabric
The fibrillation performance of silk or tin silk fabrics is tested on the fabric level by wet friction method, which solves the problem of low repeatability of fiber fibrillation performance in the prior art, and achieves accurate and stable evaluation of the degree of fiber fibrillation.
Patent Information
- Application Number
- CN202411967285.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art lacks a unified method to evaluate the fibrillation properties of fibers, resulting in low repeatability of experimental results and it is difficult to objectively quantify the fibrillation degree of fibers, especially at the fabric level.
The wet friction method is used to test the fibrillation properties of silk or tin silk fabrics. The wet friction treatment of cotton cloth forms the gray wool phenomenon on the surface of the fabric, and the degree of fibrillation is evaluated by the 1-5 level comparison of the gray sample card.
It has achieved accurate testing of fibrillation properties of silk or tin silk fabrics, with good reproducibility, simple methods, and good universality and stability.
Smart Images

Figure CN119845759A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabric fibrillation performance testing, and in particular to a method and equipment for testing the fibrillation performance of real silk or tencel fabrics. Background Art
[0002] Fibrillation refers to the phenomenon that during the processing and use of fibers or fabrics, fine fibers with a diameter of 1-4μm are separated from the fibers longitudinally through mechanical external friction, thereby forming hairiness on the surface of the yarn. Tencel and silk fibers are fiber materials that are easily fibrillated, and their fibrillation phenomenon is more obvious in a humid environment. Fibrillated fabrics are more likely to feel old and damaged during use. Silk fabrics appear white and lose their gloss, while Tencel fabrics appear white and pilling. Therefore, the silk or Tencel fabrics with better anti-fibrillation performance on the market are sold at a relatively high price; while the silk or Tencel fabrics with more serious fibrillation performance have certain limitations in their scope of application.
[0003] At present, there is no unified method for evaluating the fibrillation performance of fibers at home and abroad, which brings great difficulties to the identification of the fibrillation performance of fibers. Only relevant laboratories use ultrasonic vibration method to detect the fibrillation performance of fibers. The ultrasonic vibration method uses the interaction between the vibration probe and the fiber to simulate the friction of the fiber in actual use, and uses the number and length of the fibrils on the fiber surface after vibration to evaluate the fibrillation performance of the fiber. The advantage of the vibration method is that it is simple to operate and fast. However, since the fiber is not controlled during the vibration process, the experimental results vary greatly and the repeatability is low. Therefore, it can only be used for preliminary qualitative analysis, and it is difficult to objectively quantify the degree of fiber fibrillation. There are also studies that use the method of fixing the fiber and rubbing it tangentially with the grinding roller at a certain speed until it breaks to evaluate the fibrillation ability of the fiber.
[0004] However, the above method is only a test method for the fibrillation performance of fibers. Currently, there is no research at home and abroad to evaluate the fibrillation degree of fabrics. Summary of the invention
[0005] In order to solve the problems existing in the above-mentioned background technology, the present invention provides a method for testing the fibrillation performance of silk or tencel fabrics, which adopts a wet friction method to test the fibrillation ability of silk or tencel fabrics. The testing method is simple, and printing and dyeing factories are all capable of testing. The test is accurate, reproducible, and has good universality and stability. In addition, the present invention also provides a device for testing the fibrillation performance of silk or tencel fabrics, which has a simple structure and is easy to use.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A first aspect of the present invention provides a method for testing the fibrillation performance of a silk or tencel fabric, comprising the following steps:
[0008] S1. Cotton cloth soaking: Cut the cotton fabric, soak it with water, and press out excess water. The moisture content of the cotton fabric is kept at 80-100%. The moisture content of the cotton fabric affects the fibrillation effect after wet friction treatment. Through experiments, the moisture content of the cotton fabric is controlled within the range of 80-100%, so that the subsequent wet friction treatment forms obvious fibrillation, pilling, etc.
[0009] S2, friction treatment: under the support of a heavy object, rub the cotton cloth back and forth on the surface of the fabric sample to be tested at a certain speed, wherein the fabric sample to be tested is a silk fabric or a tencel fabric;
[0010] S3, blow-drying treatment: blow-drying the friction-treated fabric sample to be tested;
[0011] S4. Result comparison: compare the treated fabric sample to be tested with the grey sample card, and evaluate the fibrillation degree of the fabric according to the 1-5 level of the grey sample card.
[0012] Using the above technical solution:
[0013] It is observed in the present invention that both Tencel and silk fibers are fiber materials that are easily fibrillated, and their fibrillation phenomenon is more obvious in a humid environment. Therefore, the present invention chooses to use a wet friction method to test and characterize the fibrillation ability of silk or Tencel fabrics. The specific test principle is as follows: in a wet state, the Tencel or silk fabric to be tested is rubbed with cotton cloth, and the fibrillation performance of the silk or Tencel fabric is tested by utilizing the graying and fuzzing of the fabric surface caused by fiber fibrillation. The graying and fuzzing of the silk or Tencel fabric surface after the treatment is compared with the gray sample card of level 1-5, thereby realizing the evaluation of the fibrillation degree of the silk or Tencel fabric. The performance test is accurate and has good reproducibility. The test method is simple and has good universality and stability.
[0014] Furthermore, in step S2, the weight of the weight is 100 to 500 g, and the friction processing speed is 10 to 30 m / min.
[0015] During the friction treatment process, the higher the weight of the weight added and the faster the friction treatment speed, the more obvious the fibrillation degree of the fabric after wet friction treatment will be. However, if the weight of the weight added is too high and the friction treatment speed is too fast, the fabric will be worn and torn, affecting the result judgment. Therefore, after many tests, the weight of the weight added is controlled at 100-500g and the friction treatment speed is controlled at 10-30m / min, which can not only make the fabric fully wet rubbed, but also control the degree of fabric wear, without causing obvious and serious damage such as holes and tears in the fabric, and will not affect the result judgment.
[0016] Furthermore, in step S2, a heavy hammer is used to hold the cotton cloth, the end of the heavy hammer is covered with cotton cloth, and the cotton cloth is fixed to the end of the heavy hammer with a circular ring, and the bottom end surface of the heavy hammer covered with cotton cloth contacts the surface of the cloth sample to be tested for friction treatment.
[0017] Specifically, a heavy hammer is used to support a heavy object. The end of the heavy hammer is a columnar structure. A circular ring is detachably installed on the outside of the columnar structure. The cotton fabric is cut according to the size of the columnar structure at the end of the heavy hammer. It is necessary to ensure that the cotton fabric can completely cover the end of the heavy hammer. During the test, the soaked cotton cloth is wrapped around the outside of the columnar structure at the end of the heavy hammer to ensure that the cotton cloth on the bottom end face of the heavy hammer is flat. Then the circular ring is put on the outside of the cotton cloth and installed on the outer side of the columnar structure at the end of the heavy hammer to fix the cotton cloth. The height of the bottom end face of the installed circular ring is higher than the height of the bottom end face of the heavy hammer. This avoids the metal friction between the circular ring and the fabric during the friction process, which will cause damage to the fabric and affect the performance test results.
[0018] Furthermore, in the step S2, the friction treatment is performed 80 to 100 times.
[0019] Furthermore, in the step S1, the cotton fabric used is a standard cotton lining for color fastness testing, and the specification is pure cotton plain weave.
[0020] Standard cotton interlining is commonly used in cloth dyeing factories. The raw materials are easy to obtain. Compared with other interlinings such as silk and chemical fiber, the use of cotton interlining for wet grinding will result in more obvious fabric fibrillation.
[0021] Further, in step S4, the fibrillation degree of the fabric is divided into levels 1-5;
[0022] When the fibrillation degree of the fabric is level 1: the silk surface of the friction part is severely whitened, the grayscale color difference of the faded color is close to that of the gray sample card level 1, and small pilling occurs on the silk surface;
[0023] When the fibrillation degree of the fabric is level 2: the silk surface of the friction part is obviously whitened, and the grayscale color difference of the faded color is close to that of the gray card level 2;
[0024] When the fibrillation degree of the fabric is level 3: the silk surface of the friction part turns white, and the gray color difference of the faded color is close to that of the gray card level 3;
[0025] When the fibrillation degree of the fabric is level 4: the silk surface of the friction part is slightly whitened, and the grayscale color difference of the faded color is close to that of the gray card level 4;
[0026] When the fibrillation degree of the fabric is level 5: there is no obvious whitening of the silk surface at the friction part, and the fading gray color difference is close to that of the gray sample card level 5.
[0027] According to a second aspect of the present invention, there is provided a test device for the fibrillation performance of real silk or tencel fabrics, which is used in the above-mentioned test method. The test device comprises an operating table, on which a fabric sample to be tested is placed flat, and two pressing and fixing components are arranged on the operating table. The two pressing and fixing components are located on opposite sides of the operating table, and are used to press down and fix the two ends of the fabric sample to be tested on the operating table. A horizontal connecting rod is arranged directly above the operating table, one end of the connecting rod is connected to a reciprocating drive mechanism, and the other end of the connecting rod is provided with a through hole, the end of the weight passes through the through hole and extends vertically downward, the end of the weight is wrapped with soaked cotton cloth, and a circular ring is detachably provided on the outer side of the end of the weight, the circular ring fixes the cotton cloth to the end of the weight, and the bottom end surface of the weight is covered with cotton cloth, which contacts the surface of the fabric sample to be tested for friction treatment.
[0028] The pressing and fixing assembly can adopt the assembly with pressing and fixing function commonly used in the prior art. Specifically, a structure in which a pressing rod, a rotating shaft and a locking member cooperate can be adopted. The pressing rod is installed on the rotating shaft, and the rotating shaft is rotatably installed on the operating table. By rotating the rotating shaft, it drives the pressing rod to rotate and lift or rotate and press down, and then fix one end of the rotating shaft through the locking member, so as to realize the pressing and fixing of the pressing rod. In addition, in order to facilitate the installation of the cotton cloth at the end of the heavy hammer, one end of the connecting rod and the reciprocating drive mechanism adopt a rotating installation method, and an installation method that can move up and down can also be adopted. When the cotton cloth needs to be installed, the connecting rod is lifted up, and when wet friction work needs to be performed, the connecting rod is lowered down.
[0029] The specific working principle of the device is as follows:
[0030] The connecting rod and the pressing and fixing assembly are rotated and lifted, and the fabric sample to be tested is laid flat on the surface of the operating table, and then the pressing and fixing assembly is rotated and pressed down to press down and fix the two ends of the fabric sample to be tested on the operating table;
[0031] A weight of a specific weight is selected according to the fabric type, and it is installed in the through hole at the end of the connecting rod. The columnar structure at the end of the weight passes downward through the through hole, and the soaked cotton cloth is wrapped around the outside of the columnar structure at the end of the weight, and the cotton cloth on the bottom end face of the weight is ensured to be flat. Then a circular collar is put on the outside of the cotton cloth, and is installed on the outer side of the columnar structure at the end of the weight to fix the cotton cloth. The height of the bottom end face of the installed circular collar is higher than the height of the bottom end face of the weight, so as to avoid the circular collar from contacting with the fabric during the friction process, which becomes metal friction, causes damage to the fabric, and affects the performance test results.
[0032] The connecting rod is rotated and lowered, and the bottom end surface of the weight hammer contacts and presses down with the surface of the fabric sample to be tested, and the weight hammer is driven to reciprocate in a specific direction through the reciprocating drive mechanism, and the cotton cloth on the bottom end surface of the weight hammer and the surface of the fabric sample to be tested are wet rubbed back and forth;
[0033] After the wet friction treatment is completed, rotate and lift the fixing assembly, take out the friction-treated fabric sample, blow dry it with a hair dryer, compare the dust and fuzzing conditions at the wet friction-treated area on the fabric sample surface with the gray sample card, and evaluate the fibrillation degree of the fabric according to the 1-5 levels of the gray sample card, thereby achieving an objective evaluation of the fibrillation degree of silk or Tencel fabrics.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] It is observed in the present invention that both Tencel and silk fibers are fiber materials that are easily fibrillated, and their fibrillation phenomenon is more obvious in a humid environment. Therefore, the present invention chooses to use a wet friction method to test and characterize the fibrillation ability of silk or Tencel fabrics. The specific test principle is as follows: in a wet state, the Tencel or silk fabric to be tested is rubbed with cotton cloth, and the fibrillation performance of the silk or Tencel fabric is tested by utilizing the graying and fuzzing of the fabric surface caused by fiber fibrillation. The graying and fuzzing of the silk or Tencel fabric surface after the treatment is compared with the gray sample card of level 1-5, thereby realizing the evaluation of the fibrillation degree of the silk or Tencel fabric. The performance test is accurate and has good reproducibility. The test method is simple and has good universality and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0037] Figure 1 This is a real picture of the silk fabric after wet friction treatment and drying treatment in Example 1;
[0038] Figure 2 This is a real picture of the Tencel fabric after wet friction treatment and drying treatment in Example 2;
[0039] Figure 3 Schematic diagram of the structure of the fibrillation performance testing equipment for silk or tencel fabrics in Example 3.
[0040] Among them, the specific drawings are marked as:
[0041] Operating table 1, downward pressing fixing assembly 2, heavy hammer 3, circular collar 4, connecting rod 5, reciprocating driving mechanism 6. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Example 1
[0044] A method for testing the fibrillation performance of silk fabrics comprises the following steps:
[0045] S1. Soaking cotton cloth:
[0046] The cotton fabric is a standard cotton lining for color fastness testing, with a specification of pure cotton plain weave. The cotton fabric is cut into 3cm*3cm size, soaked with water, and excess water is squeezed out. The moisture content of the cotton fabric is kept at 90%;
[0047] S2. Friction treatment:
[0048] The silk fabric to be tested is silk crepe satin, item number 14394, weight 69g / m 2 .
[0049] A 400g weight is used to support the cotton cloth, and a soaked cotton cloth is used to cover the columnar structure at the end of the weight to ensure that the soaked cotton cloth on the bottom end face of the weight is flat. Then a circular collar is put on the outside of the soaked cotton cloth and installed on the outer side of the columnar structure at the end of the weight to fix the soaked cotton cloth. The height of the bottom end face of the installed circular collar is higher than the height of the bottom end face of the weight. The silk fabric to be tested is laid flat on the workbench, and the opposite ends of the silk fabric to be tested are fixed and limited. Then the bottom end face of the weight covered with cotton cloth is contacted with the surface of the silk fabric to be tested to apply pressure, and the weight is rubbed back and forth on the surface of the silk fabric at a speed of 20m / min. The number of friction treatments is 80 times, and the surface of the treated silk fabric has dust and fuzzing phenomena.
[0050] S3, Blow Drying:
[0051] The friction-treated silk fabric is blow-dried with a hair dryer;
[0052] S4. Result comparison:
[0053] The graying condition of the treated silk fabric surface was compared with the gray sample card, and the fibrillation degree of the fabric was evaluated according to the gray sample card's 1-5 levels.
[0054] The degree of fabric fibrillation can be divided into 1-5 levels;
[0055] When the fibrillation degree of the fabric is level 1: the silk surface of the friction part is severely whitened, the grayscale color difference of the faded color is close to that of the gray sample card level 1, and small pilling occurs on the silk surface;
[0056] When the fibrillation degree of the fabric is level 2: the silk surface of the friction part is obviously whitened, and the grayscale color difference of the faded color is close to that of the gray card level 2;
[0057] When the fibrillation degree of the fabric is level 3: the silk surface of the friction part turns white, and the gray color difference of the faded color is close to that of the gray card level 3;
[0058] When the fibrillation degree of the fabric is level 4: the silk surface of the friction part is slightly whitened, and the grayscale color difference of the faded color is close to that of the gray card level 4;
[0059] When the fibrillation degree of the fabric is level 5: there is no obvious whitening of the silk surface at the friction part, and the fading gray color difference is close to that of the gray sample card level 5.
[0060] The actual silk fabric after wet friction treatment and drying treatment in this embodiment 1 is shown in FIG. Figure 1 It can be seen that the silk surface of the silk fabric at the friction point is obviously whitened, and the faded gray color difference is close to level 2 of the gray sample card.
[0061] Example 2
[0062] A method for testing the fibrillation performance of Tencel fabrics comprises the following steps:
[0063] S1. Cotton cloth soaking:
[0064] The cotton fabric is a standard cotton lining for color fastness testing, with a specification of pure cotton plain weave. The cotton fabric is cut into 3cm*3cm size, soaked with water, and excess water is squeezed out. The moisture content of the cotton fabric is kept at 100%;
[0065] S2. Friction treatment:
[0066] The tested Tencel fabric is Tencel twill, with a gram weight of 160g / m 2 .
[0067] A 300g weight is used to support the cotton cloth, and the columnar structure at the end of the weight is covered with soaked cotton cloth to ensure that the soaked cotton cloth on the bottom end face of the weight is flat. Then a circular collar is put on the outside of the soaked cotton cloth and installed on the outer side of the columnar structure at the end of the weight to fix the soaked cotton cloth. The height of the bottom end face of the installed circular collar is higher than the height of the bottom end face of the weight. The Tencel fabric to be tested is laid flat on the workbench, and the opposite ends of the Tencel fabric to be tested are fixed and limited. Then the bottom end face of the weight covered with cotton cloth is contacted with the surface of the Tencel fabric to be tested and pressure is applied, and the weight is rubbed back and forth on the surface of the Tencel fabric at a speed of 20m / min. The number of friction treatments is 100 times, and the surface of the Tencel fabric after treatment has dust and fuzzing phenomena.
[0068] S3, Blow Drying:
[0069] The friction treated Tencel fabric is blow-dried with a hair dryer;
[0070] S4. Result comparison:
[0071] The graying condition of the surface of the treated Tencel fabric was compared with the gray sample card, and the fibrillation degree of the fabric was evaluated according to the 1-5 level of the gray sample card.
[0072] The actual Tencel fabric after wet friction treatment and drying treatment in Example 2 is shown in FIG. Figure 2 It can be seen that the silk surface of the friction area of the Tencel fabric is obviously whitened, and the fading gray color difference is close to level 2.5 of the gray sample card.
[0073] Example 3
[0074] A test device for the fibrillation performance of silk or tencel fabrics, used in the above test method, such as Figure 3 As shown, the testing equipment includes an operating table 1, on which a cloth sample to be tested is placed flat, and two pressing and fixing components 2 are arranged on the operating table 1, which are located on opposite sides of the operating table 1, and are used to press down and fix the two ends of the cloth sample to be tested on the operating table 1, and a horizontal connecting rod 5 is arranged directly above the operating table 1, one end of the connecting rod 5 is connected to a reciprocating driving mechanism 6, and the other end of the connecting rod 5 is provided with a through hole, and the end of a weight 3 passes through the through hole and extends vertically downward, the end of the weight 3 is wrapped with soaked cotton cloth, and a circular ring 4 is detachably provided on the outer side of the end of the weight 3, the circular ring 4 fixes the cotton cloth to the end of the weight 3, and the bottom end surface of the weight 3 is covered with cotton cloth, which contacts with the surface of the cloth sample to be tested for friction treatment.
[0075] The pressing and fixing assembly 2 can adopt the assembly with pressing and fixing function commonly used in the prior art, specifically, the structure of the pressing rod, the rotating shaft and the locking member can be adopted, the pressing rod is installed on the rotating shaft, and the rotating shaft is rotatably installed on the operating table 1, by rotating the rotating shaft, it drives the pressing rod to rotate and lift or rotate and press down, and then fix one end of the rotating shaft by the locking member, so as to realize the pressing and fixing of the pressing rod. In addition, in order to facilitate the installation of cotton cloth on the end of the heavy hammer 3, one end of the connecting rod 5 and the reciprocating drive mechanism 6 adopt a rotating installation method, and an installation method that can be moved up and down can also be adopted. When the cotton cloth needs to be installed, the connecting rod 5 is lifted up, and when wet friction work needs to be performed, the connecting rod 5 is lowered down.
[0076] The specific working principle of the device is as follows:
[0077] The connecting rod 5 and the pressing and fixing assembly 2 are rotated and lifted, and the fabric sample to be tested is laid flat on the surface of the operating table 1, and then the pressing and fixing assembly 2 is rotated and pressed down to press down and fix the two ends of the fabric sample to be tested on the operating table 1;
[0078] A weight 3 of a specific weight is selected according to the type of fabric, and is installed in the through hole at the end of the connecting rod 5. The columnar structure at the end of the weight 3 passes downward through the through hole, and the soaked cotton cloth is wrapped around the outside of the columnar structure at the end of the weight 3, and the cotton cloth outside the bottom end surface of the weight 3 is ensured to be flat. Then the circular collar 4 is put on the outside of the cotton cloth, and is installed on the outer side of the columnar structure at the end of the weight 3 to fix the cotton cloth. The height of the bottom end surface of the installed circular collar 4 is higher than the height of the bottom end surface of the weight 3, so as to avoid the circular collar 4 from contacting with the fabric during the friction process, which becomes metal friction, causes damage to the fabric, and affects the performance test results.
[0079] The connecting rod 5 is rotated and lowered, and the bottom end surface of the weight 3 contacts and presses down with the surface of the fabric sample to be tested, and the reciprocating driving mechanism 6 drives the weight 3 to reciprocate in a specific direction, and the cotton cloth on the bottom end surface of the weight 3 and the surface of the fabric sample to be tested are wet rubbed back and forth;
[0080] After the wet friction treatment is completed, rotate and lift the pressing and fixing component 2, take out the friction-treated fabric sample, blow dry it with a hair dryer, compare the dust and fuzzing conditions of the wet friction-treated area on the surface of the fabric sample with the gray sample card, and evaluate the fibrillation degree of the fabric according to the 1-5 level of the gray sample card, thereby achieving an objective evaluation of the fibrillation degree of silk or Tencel fabrics.
[0081] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for testing the fibrillation performance of silk or tencel fabrics, characterized in that: The steps include: S1. Wetting cotton cloth: Cut the cotton fabric, soak it with water, and squeeze out excess water, so that the moisture content of the cotton cloth is kept at 80-100%; S2, friction treatment: under the support of a heavy object, rub the cotton cloth back and forth on the surface of the fabric sample to be tested at a certain speed, wherein the fabric sample to be tested is a silk fabric or a tencel fabric; S3, blow-drying treatment: blow-drying the friction-treated fabric sample to be tested; S4. Result comparison: compare the treated fabric sample to be tested with the grey sample card, and evaluate the fibrillation degree of the fabric according to the 1-5 level of the grey sample card.
2. The method for testing the fibrillation performance of silk or tencel fabric according to claim 1, characterized in that: In the step S2, the weight of the weight is 100-500 g, and the friction processing speed is 10-30 m / min.
3. The method for testing the fibrillation performance of silk or tencel fabric according to claim 2, characterized in that: In step S2, a weight is used to support the cotton cloth, the end of the weight is covered with cotton cloth, and the cotton cloth is fixed to the end of the weight with a circular ring, and the bottom end surface of the weight covered with cotton cloth contacts the surface of the cloth sample to be tested for friction treatment.
4. The method for testing the fibrillation performance of silk or tencel fabric according to claim 3, characterized in that: In the step S2, the friction treatment is performed 80 to 100 times.
5. The method for testing the fibrillation performance of silk or tencel fabric according to claim 1, characterized in that: In the step S1, the cotton fabric used is a standard cotton lining for color fastness testing, and the specification is pure cotton plain weave.
6. The method for testing the fibrillation performance of silk or tencel fabric according to claim 1, characterized in that: In step S4, the fibrillation degree of the fabric is divided into levels 1-5; When the fibrillation degree of the fabric is level 1: the silk surface of the friction part is severely whitened, the grayscale color difference of the faded color is close to that of the gray sample card level 1, and small pilling occurs on the silk surface; When the fibrillation degree of the fabric is level 2: the silk surface of the friction part is obviously whitened, and the grayscale color difference of the faded color is close to that of the gray card level 2; When the fibrillation degree of the fabric is level 3: the silk surface of the friction part turns white, and the gray color difference of the faded color is close to that of the gray card level 3; When the fibrillation degree of the fabric is level 4: the silk surface of the friction part is slightly whitened, and the grayscale color difference of the faded color is close to that of the gray card level 4; When the fibrillation degree of the fabric is level 5: there is no obvious whitening of the silk surface at the friction part, and the fading gray color difference is close to that of the gray sample card level 5.
7. A test device for the fibrillation performance of silk or tencel fabrics, characterized in that: A test method for use as claimed in any one of claims 1 to 5, wherein the test equipment comprises an operating table, a cloth sample to be tested is placed flat on the operating table, two pressing and fixing components are arranged on the operating table, the two pressing and fixing components are located on opposite sides of the operating table, and are used to press down and fix the two ends of the cloth sample to be tested on the operating table, a horizontal connecting rod is arranged directly above the operating table, one end of the connecting rod is connected to a reciprocating drive mechanism, and the other end of the connecting rod is provided with a through hole, the end of the weight passes through the through hole and extends vertically downward, the end of the weight is wrapped with soaked cotton cloth, and a circular ring is detachably provided on the outer side of the end of the weight, the circular ring fixes the cotton cloth to the end of the weight, and the bottom end surface of the weight is covered with cotton cloth, which contacts the surface of the cloth sample to be tested for friction treatment.